Radiographic findings in adults with chronic cough in Nigeria - Falmata Audu Gubio; Ahmed Abubakar; Alhaji Modu Ali (Indian Journal of Health Sciences and Biomedical Research KLEU, 2018)
BACKGROUND: A cough is the major functional mechanism which is responsible for the clearance of secretions from the respiratory tract and serves as an important defense mechanism, and chest X-ray is the commonly indicated examination in this category of patients for possible diagnosis and treatment. AIMS: This study aimed at evaluating the spectrum of findings among patients presented with a chronic cough in the tropics. MATERIALS AND METHODS: A prospective study design was used to obtain data over a period of 3 months (March–May 2018). Adult patients aged 18 years and above who presented to the department with indication of chronic cough and plain posteroanterior chest radiographs with optimum diagnostic value were included in the study. All the radiographs were reported by a radiologist. The age, sex, coughing duration, lung changes, heart changes, and diagnosis were recorded. Data were analyzed using the SPSS software version 22.0. RESULTS: A total of fifty patients with a chronic cough were included in the study. The male-to-female ratio (M:F) was approximately 3:2. The mean age of the patients was 43.88 ± 19.24 years (range, 18–95 years). Forty-six (92.0%) patients were nonsmokers, while four (8%) were smokers. Radiographs of the twenty (40%) patients appeared normal, while thirty (60%) were abnormal, with lung opacities accounted for 34% and 26% for the right and left lungs, respectively. CONCLUSION: Chest X-ray in patients with a chronic cough nearly always causes detectable changes and lung opacity was the commonest lung change. These patterns corroborated with most studies that have been done.